Autoclave pre-treatment of green wastes – Effects of temperature, residence time and rotation speed on fuel properties. (1st August 2020) - Scherzinger, Marvin; Kulbeik, Tim; Kaltschmitt, Martin
Abstract: Green biomass wastes are typically characterized by various disadvantages such as low storability and limited calorific value complicating their energetic use. In order to counteract this, different heat-induced pre-treatment options came into discussion. One of these possibilities being particularly suitable for green biomass is the autoclave pre-treatment. Thus, the aim of this study was to investigate the influence of treatment temperature, residence time and rotation speed during autoclave pre-treatment of green biomass waste streams on various fuel specific characteristic values. Therefore, a 3-level and 3-factor Box-Behnken design was used. Autoclave pre-treatment was carried out in a technical-scale rotary reactor at temperatures of 130, 150 and 170 °C, residence times of 1, 2 and 3 h and rotation speeds of 5, 10 and 15 min −1 . Besides the solid products provided based on such a pre-treatment the steam phase was condensed to a large extent. Therefore, the possibility of using this liquid as a substrate for anaerobic digestion was investigated additionally. The investigations showed that the treatment temperature was found to be the main influencing parameter during autoclave pre-treatment for all statistically considered target values. Generally, an increase in temperature led to an increase of higher heating value and grindability as well as a decrease in equilibrium moisture content. An increase in residence time was found to cause an increase of higher heating value and a decrease of equilibrium moisture content, but compared to the effect of treatment temperature residence time had a much smaller effect.